THE HISTORY OF THE BUDDHIST JANAPADAS IN NADIA DISTRICT OF BENGAL: A REVIEW - Sarkar, Sujan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The history of Buddhism in Nadia district is very old. Buddhism flourished in Bengal in the sixth century BC when Goutama Buddha was engaged in the propagation of Buddhism in Eastern India. From that time BouddhaJanapadas were established in places like Tamralipta, Poundrobardhan, Ghusuri in Bengal. BouddhoJanapadas were also established in several places in Nadia. Examples include Subarnabihar, Gosthobihar, Panshila, Debagram and Alpa. It is difficult to say when these Janapadas were built. However, it is certain that BouddhaJanapadas were built in several places in Nadia due to the spread of Buddhism during the Pala rule. The Buddhist Janapadas of Nadia were built around different rivers. For example, Subarnabihar was built on the banks of Jalangi &Alakananda rivers, Gosthabihar on Chitra river, Alpa on the banks of Bhairab river. Many times it has been seen that due to the popularity of Buddhism, rivers or reservoirs have been named after the names ofthe Buddhist gods and goddesses. The naming of Anjana river, a branch of Jalangi river after the Buddhist goddess Anjana, indicates that rivers and canals had a deep connection with Buddhist culture in Nadia.This subject matter is highlighted.